The lesbian South : southern feminists, the women in print movement, and the queer literary canon - Harker, Jaime (The University of North Carolina Press, 2018)
"Much of the scholarship published on gay writers in the American South has focused on men, eliding the vibrant history of lesbian authorship and print culture. In The lesbian South, Jamie Harker explores the literature of lesbian-feminist writers, feminist print culture, presses, and bookstores in the post-1960s American South. Harker argues that lesbian presses and bookstores enabled the development of feminist reading and writing communities. These communities both challenged and nurtured lesbian writers, while also encouraging a feminist-inspired racial activism and individual autonomy"--